PENGARUH BLENDED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS IV SD NEGERI 1 METRO BARAT - Agam Prenadi; Muncarno; Dayu Rika Perdana; Nelly Astuti (STKIP Subang, 2023)
The problem of this research is that students do not understand the material online and the learning outcomes of mathematics are low. This study aims to determine the significant effect of blended learning on the mathematics learning outcomes of fourth grade students of SD Negeri 1 Metro Barat. This type of research is experimental research with quantitative research methods and non-equivalent control group design. The research population was 40 students and used the saturated sample technique. The research data were obtained from observation sheets, pre-test and post-test questions in the form of multiple choice questions that had been tested for validity and reliability. Data analysis using simple regression test. The results of simple regression analysis have a positive and significant effect on the application of blended learning on learning outcomes with the regression equation obtained Ŷ = 1,65 + 32,4 X and obtained Fcount significance test = 11.453 with n = 18 for an error level of 5% obtained Ftable is 4.41. So that Fcount > Ftable, which is 11, 453 > 4.41, it means that it is significant.